Toward uniform and controlled clinical pathways in cancer care: a qualitative description. (26th February 2019) - Numico, Gianmauro; Viale, Monica; Bellini, Roberta; Ippoliti, Roberto; Rossi, Maura; Maan, Tatiana; Carobene, Angelica; Pizzini, Andrea; Mistrangelo, Marinella; Bertetto, Oscar
Abstract: Quality issue: The definition of clinical pathways (CPs) and their application are heterogeneous. Each center is used to choose whether to adopt this instrument or not and to variably conceive its features We consider CPs as the necessary description of the cancer patient journey and we emphasize their role as the user view of clinical processes rather than a local translation of guidelines. Choice of solution: We proposed a unique CPs model for all the centers of our regional network, with the aim of making CPs accountable and comparable. We also established a central quality evaluation. Implementation: Through a multi-step process, the model was proposed to the 22 Regional centers. Landmark characteristics of the project were: the involvement of hospital administrations; reference to a unique set of guidelines; a peer-review and open evaluation. Evaluation: Of the 374 expected CPs, 253 (68%) were received and evaluated. A median number of 131 items were the object of evaluation in each hub center and 77 in each spoke center. About 79.5% items were considered well described, 15.5% were absent and 5.0% partially described. The median percentage of fulfilled indicators was 85.6% in hub CPs and 82.2% in spoke CPs. Although, not all diseases were equally covered through the territory a high degree of homogeneity and a good quality of compilation were achieved. Lessons learned: The project was shown to be feasible and achieved its goal. We suggest this process as a functional way for building uniform cancer CPs.